Adsorption of a water soluble cationic dye into a cationic Langmuir monolayer. (May 2015) - Shil, Ashis; Hussain, S.A.; Bhattacharjee, D.
Abstract: This communication reports the successful adsorption of a water soluble cationic fluorescent dye Rhodamine B (RhB) into a cationic Langmuir monolayer of Octadecylamine (ODA). Anionic nano clay platelets Hectorite played an important role in the process of adsorption. Surface pressure vs. area per molecule (π–A) isotherms were studied to monitor the adsorption process. In-situ fluorescence Imaging Microscopic (FIM) technique was employed to visualize the domain structures formed at the air–water interface. Atomic Force Microscopic (AFM) image of the monolayer Langmuir–Blodgett (LB) films were taken to study the morphology and ultrastructure of the film. Detailed spectroscopic investigations were carried out on the mono- and multilayer Langmuir–Blodgett (LB) films. Graphical abstract: Fluorescence Imaging Micrographs (FIM) of ODA-Clay-RhB hybrid monolayer at the air–water interface, at lower to higher surface pressures. Highlights: Adsorption of cationic molecules into cationic Langmuir monolayer. Importance of nano clay platelets in the process of adsorption. Fluorescence microscopic images (FIM) of Langmuir monolayer. Atomic Force Microscopic (AFM) image of monolayer Langmuir–Blodgett film. Spectroscopic studies of hybrid Langmuir–Blodgett films.